Symptom-Hemodynamic Mismatch and Heart Failure Event Risk. Issue 5 (September 2015) - Lee, Christopher S.; Hiatt, Shirin O.; Denfeld, Quin E.; Mudd, James O.; Chien, Christopher; Gelow, Jill M.
Abstract : Background: Heart failure (HF) is a heterogeneous condition of both symptoms and hemodynamics. Objective: The goals of this study were to identify distinct profiles among integrated data on physical and psychological symptoms and hemodynamics and quantify differences in 180-day event risk among observed profiles. Methods: A secondary analysis of data collected during 2 prospective cohort studies by a single group of investigators was performed. Latent class mixture modeling was used to identify distinct symptom-hemodynamic profiles. Cox proportional hazards modeling was used to quantify difference in event risk (HF emergency visit, hospitalization, or death) among profiles. Results: The mean age (n = 291) was 57 ± 13 years, 38% were female, and 61% had class III/IV HF. Three distinct symptom-hemodynamic profiles were identified: 17.9% of patients had concordant symptoms and hemodynamics (ie, moderate physical and psychological symptoms matched the comparatively good hemodynamic profile), 17.9% had severe symptoms and average hemodynamics, and 64.2% had poor hemodynamics and mild symptoms. Compared with those in the concordant profile, both profiles of symptom-hemodynamic mismatch were associated with a markedly increased event risk (severe symptoms hazards ratio, 3.38; P = .033; poor hemodynamics hazards ratio, 3.48; P = .016). Conclusions: A minority of adults with HF have concordant symptoms and hemodynamics. Either profile of symptom-hemodynamic mismatch in HF is associated with a greater risk of healthcare utilization for HF or death.